A Duty to Cognitively Enhance Animals. (1st April 2018) - Rohwer, Yasha
Abstract : In this article I argue that humans have a pro tanto duty to cognitively enhance some animals threatened with extinction. I will use as a case study a particular set of animals: smaller Australian marsupials. Many of these animals are on the brink of extinction thanks to the introduction of the fox and the domestic cat to the continent of Australia. Ecologists conjecture that these marsupials do not have the behavioural flexibility to cope with these introduced predators. By introducing predators, humans performed a wrong action because it led to the extinction of species and continues to threaten many marsupials species such as woylies, Gilbert's potoroos, numbats and mountain pygmy possums. This wrong action gives rise to an obligation to intervene to prevent further species loss. Traditional means of conservation do not seem sufficient to address this obligation; therefore, there is a duty to cognitively enhance these creatures as soon as the technology is sufficiently researched and safe.